Self-transferable plasmids determining the hemolysin and bacteriocin of Streptococcus faecalis var. zymogenes. - Jacob, A E (1975)
Strains of Streptococcus faecalis var. zymogenes, designated JH1 and JH3, produced a hemolysin and a bacteriocin. Hemolytic activity was lost from a low percentage of cells grown in broth at either 37 or 45 C. All nonhemolytic (Hly-) variants had lost bacteriocin activity (Ben-), and those from strain JH3 had also lost resistance to the bacteriocin (Bnr-). The majority of Hly-, Ben- variants from JH1 retained bacteriocin resistance (Bnrplus). Strains JH1 and JH3 contained a plasmid deoxyribonucleic acid species of molecular weight 38 times 10-6 (plasmids pJH2 and pJH3, respectively), and strain JH1 also contained a 50 times 10-6 molecular weight plasmid (pJH1) which has previously been shown to carry the genes determining resistance to the antibiotics kanamycin, neomycin, streptomycin, erythromycin, and tetracycline. Hly-, Bcn-, Bnr- variants of strain JH3 had completely lost plasmid pJH3. Hly-, Bcn-, Bnr- variants of strain JH1 had completely lost plasmid pJH2 and retained plasmid pJH1, but Hly-, Bcn-, Bnrplus variants had retained both plasmids pJH2 and pJH1. The Hlyplus, Bcnplus, Bnrplus traits from both parental strains were transferable to nonhemolytic S. faecalis strains during mixed incubation in broth at 37 C, and hemolytic recipient strains were found to have received plasmid pJH2 from strain JH1 and pJH3 from JH3. We conclude that the Hlyplus, Bnrplus traits are borne on plasmid pJH2 in strain JH1 and pJH3 in strain JH3 and that, in Hly-, Bcn-, Bnrplus variants of strain JH1, plasmic pJH2 has suffered a mutation affecting hemolysin and bacteriocin expression. We infer that the plasmids transfer by conjugation. Beta-hemolytic activity is the only property distinguishing the zymogenes variety from S. faecalis. Since we have shown that this activity is plasmid borne in strains JH1 and JH3, we endorse the view that the varietal status of zymogenes should be dropped.